Pengaruh Penambahan Ekstrak Inulin Umbi Dahlia terhadap Karakteristik Organoleptik Sinbiotik Set Yoghurt - Meri Novia Nurman; Minda Azhar; Fitri Amelia; Budhi Oktavia (Departemen Kimia FMIPA UNP, 2020)
Synbiotic set yoghurt with the addition of an extract of inulin from dahlia tubers can increase the functional value of yoghurt. This study aims to determine the effect of inulin addition on the organoleptic characteristics of synbiotic set yoghurt. The method of research was the experimentation method. Synbiotic set yoghurt with the addition of an extract of inulin from dahlia tubers made by variation of the concentrations of 0.1%, 0.3% and 0.5%. Incubation was performed at 37°C for 20 hours . The organoleptic tests were conducted by 15 panelists on the color, aroma and texture of set yoghurt. Organoleptic data was processed using Wilcoxon test with significant level 95% (α = 0.05). Organoleptic set yoghurt showed that the addition of 0.3% inulin significantly affect the aroma of the yoghurt sour and the texture was more dense than the yoghurt comparison. The color of the set yoghurt produced slightly more white than the set yoghurt comparison, but no significant effect on α = 0.05. The results showed that the addition of 0.3% inulin dahlia tuber extract into the set yoghurt had a significantly affect the aroma and the texture of set yoghurt, and did not significantly affect the color of set yoghurt.